Description of the ultrasonographic characteristics of the abdominal organs of the white-fronted capuchin (Cebus albifrons) - Grandez R., Ricardo (2021)
The white machín, Cebus albifrons, is a neotropical primate belonging to the Family Cebidae, Subfamily Cebinae. The aim of this study was to determine the ultrasound characteristics and the dimensions of the abdominal organs of the white-fronted capuchin in captivity. It was used four intact adult male specimens in captivity at the Huachipa Zoo and three captive specimens at the Parque de las Leyendas Board of Trustees Zoo (an adult male castrated, an adult female and a juvenile male), both institutions in the city of Lima, Peru. The specimens fasted for six hours; then physical and chemical restraint was carried out using the immobilization protocol established by each zoo. The Pie Medical 100 Falco Vet® ultrasound equipment with 7.5 MHz multifrequential convex transducer and ESAOTE MyLab One Vet with the 4-9 MHz SC312 microconvex transducer were used. The ultrasound images are displayed, and the data are presented by descriptive statistics. It is concluded that the ultrasound characteristics and the dimensions of the abdominal organs of C. albifrons are similar to those described for other species of the Cebinae Subfamily, small canines and domestic felines. The ovaries and testes were described for the first time in specimens of the Cebinae Subfamily and show similarity to that described in small canines and domestic cats.